Compensation for Fraud (Gambling) Operations Under The Guise of Investment – Restitution as A Complex or Easy Way Out Mechanism? (Learning From Various Restitution And Law Cases In Indonesia) - Yohanes Firmansyah; Imam Haryanto; Tubagus Andri Purnama; Edwin Destra (East Asian Journal of Multidisciplinary Research, 2022)
The phenomenon of Foreign Exchange (Forex) that runs in the investment sector and can help the development of Indonesia. Currently, forex has become an endemic trend and has attracted the attention of many parties, both investors and the public in general. Foreign exchange or forex is a type of trade or transaction that trades the currency of a country against the currencies of other countries involving the main money markets in the world for 24 hours continuously, so in this case a legal protection is needed. Lately, it turns out that there are many cases of fake investments in the form of gambling under the guise of investment that have claimed many victims. The purpose of this study is to find out how to guarantee legal protection for the rights of victims of criminal acts and how to provide compensation and restitution mechanisms for victims of criminal acts of fraud (gambling under the guise of investment). Through normative legal research, it is concluded: 1. Legal protection guarantees for the rights of victims of criminal acts are very important considering that the consequences of criminal acts can cause a person to experience physical, psychological and property losses and suffering. Through the legislation guaranteeing the protection of the rights of victims, it is necessary to obtain legal certainty and justice as a result of the occurrence of a crime. 2. The mechanism for providing compensation and restitution to victims of criminal acts has been regulated in Government regulations no. 44 of 2008 concerning the Provision of Compensation, Restitution, and Assistance to Witnesses and Victims, which is the implementation of Law no. 13 of 2006. 3. Another alternative to the provision of restitution and compensation that can bridge the two sides, namely the victim and the state, is to provide compensation through the issuance of State Securities which can make the victim receive compensation, and the state gets an injection of funds in terms of development without hurt both sides